Axiomatic Marxian exploitation theory: A survey of the recent literature - Rylan Chinnock; Roberto Veneziani; Naoki Yoshihara (Queen Mary University of London, School of Economics and Finance, 2024)
In this paper we review recent developments in axiomatic studies of Marxian exploitation theory. First, given the acute controversy over the formal definition of exploitation during the 1970-1990s, we review the study of the axiomatic framework, which identifies some fundamental properties - technically, domain conditions - that any definition of exploitation should satisfy. Moreover, we provide a survey on the axiomatic studies about the proper measures of exploitation which coherently preserve the basic Marxian perceptions represented by two axioms, Profit-Exploitation Correspondence Principle and Class-Exploitation Correspondence Principle. Finally, we examine the relevance of the labour theory of value in these axiomatic studies of the proper measures of exploitation.
Keywords: D63; D51; 330; Axiomatic analysis; Labour Exploitation; Profit-Exploitation Correspondence Principle; Class-Exploitation Correspondence Principle; Labour Theory of Value